Experience in regional cooperation to overcome poverty (The Network [S.l.], 1998)
Offers a general overview of the context in which the Social Network of Latin america and the Caribbean arose. Shows achievements, obstacles and limitations in the activity to strengthen relations of bilateral and regional cooperation.
Bibliography: p. 35